2018
DOI: 10.1080/17518423.2018.1460769
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological measures of stress in caregivers of individuals with autism spectrum disorder: a systematic review

Abstract: Findings suggested dysfunction of the hypothalamic-pituitary-adrenal-axis and autonomic nervous system for some, but not all, parents of children with ASD. Further research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Forty-five mothers (53.6%) reported moderate to severe burden, while only 3 mothers (3.5%) reported no burden. The findings are supported by Padden et al [20], Sabih and Sajid [21], and Ishtaiq et al [2], reporting a signifi-cant level of stress in parents of ASD children. Firdouset al [22] also recounted more stress in parents of children with intellectual disabilities than mothers of hearingimpaired children.…”
Section: Discussionsupporting
confidence: 72%
“…Forty-five mothers (53.6%) reported moderate to severe burden, while only 3 mothers (3.5%) reported no burden. The findings are supported by Padden et al [20], Sabih and Sajid [21], and Ishtaiq et al [2], reporting a signifi-cant level of stress in parents of ASD children. Firdouset al [22] also recounted more stress in parents of children with intellectual disabilities than mothers of hearingimpaired children.…”
Section: Discussionsupporting
confidence: 72%
“…In terms of cortisol reactivity to stress, findings from this study showed that lower cortisol stress reactivity was associated with obesity and the risk of becoming obese and with symptoms of depression and anxiety (see de Rooij, 2013). Numerous other recent studies have also been published that show that low or blunted cortisol reactivity to stress is associated with high levels of chronic stress, and increased risk of negative physical and mental health outcomes (e.g., Lovallo et al, 2019;O'Connor et al, 2017;Padden, Concialdi-McGlynn, & Lydon, 2019;Zorn et al 2017).…”
Section: Cortisol Responses To Stress and Future Health Riskmentioning
confidence: 58%
“…The stressors associated with parenting a child with ASD have additional negative consequences for parent and child health outcomes. Parents of children with ASD are likely to display atypical cortisol patterns, a biological marker of increased stress (Lovell et al 2015;Padden et al 2018). Heightened stress is related to poor health outcomes from autonomic nervous system dysfunction in this growing population, such as maternal depression in parents of children with ASD (Foody et al 2015;Weitlauf et al 2014).…”
Section: Introductionmentioning
confidence: 99%